Is Nigeria Ripe for Break Up? The Mitigating Importance of Cameroon and France in the Survival of Nigeria’s Territorial Integrity - Tindo, Kaze; Ndobegang, Michael (Journal of Central and Eastern European African Studies, 2024)
The major challenges which threaten the territorial integrity of Nigeria, black Africa’s political and economic giant are very unsettling but appear insufficient to predict the country’s imminent balkanization. Mindful of the threat from inside Cameroon and the vested role of France, there seems to be an uneasy reprieve that could make Nigeria the sick man of the West Central African region in the near future. This paper analyses how Nigeria’s successful manipulation of her relations with Cameroon and France may help forestall the country’s breakup. It argues that the support and friendship of other countries may not cure Nigeria’s woes but plunge it into prolonged instability. The emergence of armed separatist movements known as ‘‘Ambazonia’’ in the northwest and southwest regions of Cameroon some of whom seeking alliances with their Nigerian as a result of their ideological and geographical proximity has potential fateful consequences. On the other hand, French economic and strategic interests which expose the marginalization decried by Nigerian secessionist groups sustain the disintegration agenda. How does Nigeria react in the face of outreach initiatives by Cameroonian separatist movements? How does Nigeria exploit France’s privileged relationship with Cameroon to save itself from disintegration? This contribution concludes that Nigeria’s relationship with other countries may not solve its problems but transform the country into a long-term theatre of instability.